«Ажал тек адамға ғана тиді»: ғаламдық пандемия кезінде М. Шеллидің «Соңғы адам» фильмін қайталау - Ch., Keeling (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2020)
There are many works of literature which give us detailed accounts of plague, as epidemic and even pandemic (Decameron, Journal of a Plague Year, The Plague). However, Mary Shelley’s The Last Man is the first plague narrative to depict a global pandemic. Moreover, it interrogates a world before nineteenth-century globalization by prophesying a future in 2073. Shelley’s frame narrative shows the reader an alternate history where the hegemony of free-market capitalism and Darwinian evolutionary science do not exist. What can this fictional world without capitalism and evolutionary theory tell us? This article engages in a qualitative critical analysis of The Last Man from the field of literature and science. First, as a novel, Shelley addresses both the individual perspective of the isolated narrator-witness, and, at a wider level, the society that dissolves around the protagonist. This literary unpacking of the novel suggests McKeon’s naïve and sceptical empiricism as useful in interrogating both fictionality and any basis for interpretation of empirical, factual evidence mediated through human narrative in the text. Second, Shelley draws on the competing theories of proto-evolutionary science of the 1820s: Huttonian eternalism, Cuvierian catastrophism and Lamarckian transformism. Shelley’s reworkings of nineteenthcentury natural philosophy allow us to re-evaluate our relationship with nature from a paradigm before evolutionary theory. This history-of-science approach interrogates the novel as both methodology and content. Indeed, I argue that Shelley’s proto science fiction classic can help us re-interrogate our own dominant cultural and ideological assumptions in the midst of the current Covid-19 global pandemic. Key words: Pandemic, Covid-19, Shelley, frame narrative, naïve and sceptical empiricism, protoevolutionary science, Hutton, Cuvier, Lamarck, eternalism, catastrophism, transformism